Fungal sinusitis clinical presentation, latest management: A Review Update - Bhowmik, Bithi (Journal of Science Foundation, 2015)
Fungal sinusitis is a relatively common, often misdiagnosed disease process involving the paranasal sinuses. It is a serious condition, as certain forms of fungal sinusitis are associated with a high rate of mortality. Successful treatment requires a prompt diagnosis and frequently relies on radiologic imaging, specifically computed tomography (CT) and magnetic resonance (MR) imaging. The classification of fungal sinusitis is ever changing, but under the most current and widely accepted classification fungal sinusitis is broadly categorized as either invasive or noninvasive. Invasive fungal sinusitis is defined by the presence of fungal hyphae within the mucosa, submucosa, bone, or blood vessels of the paranasal sinuses. Invasive fungal sinusitis is subdivided into acute invasive fungal sinusitis, chronic invasive fungal sinusitis, and chronic granulomatous invasive fungal sinusitis. Conversely, noninvasive fungal sinusitis is defined by the absence of hyphae within the mucosal and other tissues of the paranasal sinuses. Noninvasive fungal sinusitis is subdivided into allergic fungal sinusitis and fungus ball (fungal mycetoma). Journal of Science Foundation, 2014;12(1):16-19